What, if anything at all, do African societies themselves owe to their own citizens in terms of health? - Thierry Ngosso (BMC, 2023)
Abstract The debate about global justice and health has focused so far on what developed countries owe to developing countries to advance global public health. Less attention has however been paid to the health obligations of developing countries, especially in Sub-Saharan Africa, towards their own people and how this may affect considerations about justice and health in a globalized world. This paper challenges the implicit presumption in global justice theories that African societies, because they are poor, have weaker health obligations toward their own peoples. It makes two main claims. First, despite their economic shortcomings, African governments should have the primary responsibility to protect the domestic side of the human right to health of their own citizens and dumping their own health obligations on rich countries is a disservice to the overall goal of global justice in health. Second, the health obligations of African societies towards their own people should be assessed and grounded also on their potential abilities, and not exclusively on their current abilities. Global justice in health cannot be reduced to what rich countries should do. It must include also what developing countries from Sub-Saharan Africa should do beyond accepting or managing any health assistance.